Functional Kompiang Bread with Sardine Flour: Sensory Acceptance and Nutritional Properties - Friend Zakharia; Boiris Milyardo; Theodora Fernandez; Dewi Lina Lumban Gaol; Laurensius Sandro Rero; Aida Fitria (Jurnal Pemberdayaan Masyarakat, 2025)
This study aims to enhance the nutritional value of kompiang bread by adding sardine flour. The goal was to increase its calcium content. Sardines are a nutritious and widely accessible fortification option. A 4D Research and Development model was used to create four bread variants: P1 (5% sardine flour), P2 (10% sardine flour), P3 (15% sardine flour), and a control without sardine flour. Sensory attributes evaluated included color, aroma, taste, and texture. Nutritional parameters assessed were moisture, ash, fat, fiber, protein, and carbohydrates. Adding sardine flour changed the color, taste, texture, and aroma of the bread. It also increased ash, protein, fat, and calcium content, while reducing carbohydrates and moisture. The P3 variant, which contained 15% sardine flour, had the best nutritional profile. It provided 10.01 grams of protein, 1.64 grams of fat, 24.47 grams of carbohydrates, and 10.01 grams of calcium per 40-gram serving. These results suggest that fortifying kompiang bread with sardine flour is a practical and sustainable method for creating calcium-rich foods. This approach may support improved public health nutrition.